Một số đặc điểm sinh khí hậu các đảo ven bờ Việt Nam - Vân, Nguyễn Khanh; Hiền, Nguyễn Thị; Lộc, Phan Kế; Hiệp, Nguyễn Tiến (Vietnam Journal of Earth Sciences, 2018)
Some features of bioclimatic condition in the islands...